Disease transmission in animal transfer networks - Sintayehu, Dejene W.; Prins, H.H.T.; Heitkönig, I.M.A.; de Boer, W.F. (Preventive veterinary medicine, 2017)
Infectious diseases transmission is strongly determined by who contacts whom. Bovine tuberculosis (bTB) caused by Mycobacterium bovis is a worldwide burden for animal populations. One of the major transmission mechanism between herd is the transfer of infectious animal. In East Africa, pastoralists may receive or bestow livestock to create and strengthen social relationships. Here, we used a network approach to examine the relative importance of such cattle transfer in the transmission of bTB. First, a total of 2550 cattle from 102 herds were tested using the comparative intradermal tuberculin test to assess the presence of bTB infected cattle in the herd. A herd was considered bTB positive if it had at least one tuberculin reactor animal. Next, we calculated the centrality of each herd in the cattle transfer network using four established measures of social network centralization: degree, betweenness, closeness and fragmentation. The relationships between the network centrality measures and bTB infection were examined using generalized linear mixed models (GLMM). We found that a herd’s in-degree in the social network was positively correlated with the risk of being infected with bTB (b=4.2, 95%CI=2.1–5.7; p<0.001). A herd that was close to many others (i.e., had a higher closeness index) had a larger chance of acquiring bTB infection (b=2.1, 95%CI=1.4–2.8; p<0.001). Betweenness centrality was also positively associated with the presence of bTB infection. There was a negative relationship between the fragmentation index and bTB infection (b=−2.7, 95%CI=−4.9–1.3; p<0.001). The study clearly demonstrated that the extent to which a herd is connected within a network has significant implications for its probability of being infected. Further, the results are in accordance with our expectation that connectivity and the probability that a herd will transmit the disease to other herds in the network are related.